Assessment of quality of life in IPF Patients: a multicenter observational study - Uzer, Fatih; Cilli, Aykut; Hanta, Ismail; Coskun, Funda; Sevinc, Can; Ursavaş, Ahmet; Leblebici, Asim; Yilmaz, Gozde; Yazici Celik, Gamze; Kamel, Ibrahim (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Aim: This study aimed to examine how dyspnea, cough, sleep disruption, anxiety, depression, and physiological factors affect the quality of life in newly diagnosed, untreated IPF patients. Methods: This study is a multicenter observational study. Patients not receiving antifibrotic treatment were included. To assess patients’ quality of life, Leicester Cough Questionnaire (LCQ), St. George’s Respiratory Questionnaire (SGRQ), Short Form-36 (SF-36), Hospital Anxiety and Depression Scale (HADS), Borg Dyspnea Index (BDI), Modified Medical Research Council Dyspnea Scale (MMRC) score, Composite Physiological Index (CPI), Gender Age and physiology (GAP) score, and Pittsburgh Sleep Quality Index (PSQI) were administered. Results: Among 88 patients (mean age: 67.6±8.5 years), 81.9% were diagnosed with IPF through HRCT, 14.8% through surgery, and 3.4% via cryobiopsy. The average disease duration was 2.2±2.9 years. Over 50% experienced moderate to severe depression, and 40% had moderate to severe anxiety. In the IPF group, 13.6% had possible usual interstitial pneumonia (UIP), and 81.8% had definite UIP pattern. No significant differences were found between UIP groups in various scores. Anxiety and depression correlated negatively with respiratory function and positively with MMRC score and BDI. Sleep quality scores had similar correlations. Patients with good sleep quality had better respiratory parameters (p=0.013), lower MMRC (p=0.004), BDI (p=0.026), and CPI (p=0.047). Conclusion: A notable number of IPF patients in follow-up show symptoms of anxiety and depression. Moreover, declining respiratory function not only diminishes sleep quality but also elevates dyspnea scores.